BIODEGRADATION OF POLYBLEND POLYPROPILENE- PALM OIL-AMYLUM BY Bacillus subtilus AND Clostridium botulinum - Zainal Fanani; Miksusanti Miksusanti; Desnelli Desnelli (Universitas Gadjah Mada, 2003)
It had been done a biodegradation polyblend from blending polypropilene-palm oil-amylum with three composition of polyblend i.e polyblend A 80% polypropilene- 19.5% palm oil- 0.5% amylum, poliblend B 80% polypropilene- 19% palm oil- 1% amylum and polyblend C 80% polypropilene-18% palm oil- 2% amylum by B. subtilus and C. botulinum, time incubation was twenty five days. The characterization of polyblend before and after biodegradation has done with FTIR, DTA, Viscometre and tensile strength of polyblend. The result showed that Bacillus subtilus and Clostridium botulinum can biodegradate polyblend and make holes as well as chink on polyblend especially polyblend C, because it has more carbohidrat than polyblend A and B. Analysis from FTIR showed compatible of poliblend because it did not have a new function group and did not change of wavelength. Data of tensile strength showed lower value after biodegradation at polyblend C and from DTA and Viscometre showed lower melting point and lower average molecule weight, respectively.